ANALISIS PENATAUSAHAAN BARANG MILIK NEGARA MELALUI PENGGUNAAN APLIKASI SIMAK-BMN PADA KANTOR KEMENTERIAN AGAMA KABUPATEN MINAHASA - Gubali, Martikawati; Tinangon, Jantje; Pusung, Rudy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The administering State-owned Goods is a series of activities which include bookkeeping, inventory, reporting State-owned Goods in accordance with the provisions of the legislation which is aimed, namely the embody an orderly administration and support orderly management of the State-owned Goods, then adherence to legislation is absolutely necessary. This research aims to know the application of the administering BMN managed Office Ministry of Religion in accordance with PMK Number 181 Years 2016 through the application SIMAK-BMN accordance with PMK Number 213 Year 2013 as it has been updated with PMK, number 215 year 2016. The method used is descriptive analysis method. The results of the research indicates that the application of the administering Office work unit at BMN Ministry of Religion were in accordance with regulation of the Minister of finance Number 181 Year 2016 about Administering BMN, with percentage suitability of 73.68% average. Registration BMN through SIMAK- BMN has been accordance to the number 213 Years PMK 2013 as it has been updated with a 215 Year Number 2016 FMD on accounting systems and financial reporting to the Central Government with the percentage compliance 85.71%. Keywords: Administering State-Owned Goods